Effects Of Pre-Treatments On The Physicochemical And Functional Properties Of Musa Acuminata X Balbisiana Cv. Awak Flour - Chong, Li Choo (2011)
This research was carried out to pre-treated the plantain Awak slices with conventional methods: ascorbic acid (AA) (0.5 %, 1 %, 2 %), L-cysteine (L-cys) (0.5 %, 1 %, 2 %) and blanching (60 oC / 10 min, 60 oC / 20 min, 70 oC / 10 min, 70 oC / 20 min, 75 oC / 10 min dan 75 oC / 20 min), in line with the objective of elucidating the effect of pre-treatments on the physico-chemical and functional properties of Awak flour produced. Chemical pre-treatments (AA and L-cys), especially L-cys (1 %) retained the highest phenolic compounds and antioxidant properties in the flour. High temperature blanching (70 oC – 75 oC) destroyed certain amount of phenolic compounds and reduced the antioxidant power. AA and L-cys pre-treatments, especially at 2 % solution were found to induce depolymerization of amylopectin chains and facilitated the water binding ability of plantain starches. This phenomenon was indicated by higher water activity, swelling power, flow behaviour index and higher paste viscosity of Awak flour. Similar observation was found in Awak flour obtained from low blanching temperature pre-treatment (60 oC and 65 oC), which resulted in weakening of starch flexibility and polysaccharide bonding. Granular structure of starches extracted from pre-treated Awak slices were shown to remain intact but cracks were observed in the SEM study. These structural changes reflected higher in-vitro starch digestibility (IVSD) and lower thermal behaviour of Awak flour. In Fourier transform infrared (FTIR) spectroscopy test, IR spectra of pre-treated Awak flour did not change significantly.